If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-18 + 6x) = -36 (-18 * -2 + 6x * -2) = -36 (36 + -12x) = -36 Solving 36 + -12x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -12x = -36 + -36 Combine like terms: 36 + -36 = 0 0 + -12x = -36 + -36 -12x = -36 + -36 Combine like terms: -36 + -36 = -72 -12x = -72 Divide each side by '-12'. x = 6 Simplifying x = 6
| 8+2e=-20 | | 1(n+1)2(n+1)3(n+3)=80 | | x+8y=-9 | | -3x-6y=15 | | x=.0002x^2-.316(750)+127.9 | | .666666x-7=11 | | 3b+(b-3)= | | 127+6x+2+x=180 | | 7a+13+3a=27-20a+6 | | 134=-3x-7(3x-2) | | 1(n+1)2(n+2)3(n+3)=80 | | 2x+8+5x-10+5x-10=180 | | 5x+64=6x-14 | | 2.5z=13.9 | | -7(r+4)+5(4r-2)=40 | | 2n(q-4x)=6m | | Log[5](x+12)+Log[5](x-12)=2 | | -125*-2= | | 54-4x=-177+7x | | -5x^2=6 | | 24=-7(6b+8) | | 7(2+3x)=182 | | C=3.14*21 | | x=.0002x^2-.316x+127.9 | | 3(m-1)=6(m+2) | | 12=n/7 | | 80+25m=50+15m | | h+-538=-799 | | 12=3z+8 | | 41+10x+41+20x=640 | | 498=b+-39 | | M/9=9 |